SHADOWING TECHNIQUE (SHADOW REPEAT, ECHO REPEAT) WHEN TEACHING LISTENING IN A FOREIGN LANGUAGE - Shakirov, Rustam (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
The shadowing technique (shadow repeat, echo repeat) is a highly effective method for developing listening comprehension, pronunciation, and fluency in foreign language learning. Unlike traditional passive listening exercises, shadowing requires learners to actively repeat spoken language in real-time, reinforcing their auditory processing and speech production skills. This article explores the importance, effectiveness, and challenges of shadowing in language education. A comparative analysis demonstrates its superiority over dictation, repetition drills, and translation-based methods. Additionally, the article presents research findings, practical applications, and strategies for overcoming difficulties such as speech speed, cognitive overload, and pronunciation barriers. By integrating structured practice, speech analysis tools, and adaptive learning approaches, shadowing can significantly enhance fluency, confidence, and real-world communication skills. The study concludes that shadowing is a transformative technique that should be incorporated into modern language teaching methodologies to improve learners’ listening and speaking abilities.